Correlation of structural and electrophysiological changes in the retina of young high myopes. (November 2014) - Koh, Victor; Tan, Clement; Nah, Gerard; Zhao, Paul; Yang, Adeline; Lin, Sheng Tong; Wong, Tien Yin; Saw, Seang Mei; Chia, Audrey
Abstract Purpose Despite a high prevalence of myopia among young East Asian adults, there is a lack of data on the myopic retina structure‐function relationship in this group. We examined the association between optical coherence tomography (OCT) and electroretinogram (ERG) measurements in highly myopic young Asian adults to provide this information and also determined if OCT can be used as an alternative screening tool to assess retinal function in young myopic adults. Methods This was a prospective study comprising young adults aged between 18 and 25 years with spherical equivalent refraction of worse than −6.00 D. A comprehensive ophthalmic examination comprising fundus examination and grading, ocular biometry, time‐domain OCT (fovea, macular and retinal nerve fibre layer thickness) and ERG (full field and multifocal) were performed for all the eyes. Results A total of 32 eyes (mean spherical equivalent ± standard deviation −10.17 ± 1.51 D, mean age 23.8 ± 1.3 years) were included. None of the eyes showed visible myopic retinopathy and the central retina thickness of all eyes was classified as within the normal range. Full‐field ERG amplitude and multifocal ERG P1 amplitudes in the outer rings (R3‐R5) were, however, inversely associated with axial length. The multifocal ERG P1 amplitudes were also positively correlated with mean retinal nerve fibre layer thickness in R2, 4, 5 rings and outer macular thickness in R 2–5 rings. Conclusion These findings suggest that full field ERG changes may precede fundus and OCT changes in highly myopic young adults. Although there was some correlation between multifocal ERG amplitudes with OCT outer macular and retinal nerve fibre layer thickness, the OCT may not be useful as a retinal function screening tool, being within normal limits in all eyes. Further longitudinal studies are required to determine how the relationship between ERG and OCT will evolve over time.